Implementation of Augmented Physics Animation Integrated Crosscutting Concept COVID 19 in Facilitating Problem Solving Skills and Disaster Preparedness - Yudi Guntara; Indri Sari Utami (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2021)
This study aimed to implement augmented physics animation integrated crosscutting concept COVID-19 in facilitating student problem-solving skills and disaster preparedness. This study used a quantitative approach. The research design chosen was a pre-experimental design with a posttest-only design with nonequivalent groups. The research was conducted at the Department of Physics Education, Universitas Sultan Ageng Tirtayasa. All students of the department are the research population. The sampling technique used was purposive sampling. The number of 35 students entered the experimental group, and 36 students entered the comparison group. The results showed that a) there was no difference in students' mastery of problem-solving skills in the experimental and comparison group. Asymp. Sig indicates a value of 0.187 or > 0.05, so it can be decided that H1 was rejected. b) There was a difference in the level of student COVID-19 disaster preparedness between the experimental and the comparison group. Asymp indicated this. Sig was 0.012 or < 0.05, so it could be decided that H2 was accepted. Therefore, it can be concluded that the implementation of augmented physics animation on the mastery of student problem-solving skills has not yet been seen but can already be seen in facilitating the level of preparedness of students in dealing with the COVID-19 disaster.